The relationship between reported domestic canine parvovirus cases and wild canid distribution - Van Arkel, Alicia (Heliyon, 2019)
Canine parvovirus (CPV) is an important and often fatal pathogen of domestic dogs. It is resistant in the environment and cross-species transmission has been indicated in some canid populations, but never in Australia. The aim of this study was to determine if an association exists between 1. reported CPV cases in domestic dogs, and 2. the wild canid distribution in New South Wales (NSW), Australia. Reported CPV cases, and reports of the presence of wild dogs and the red fox (Vulpes vulpes), were extracted from a voluntary surveillance database and a voluntary pest reporting system, respectively. A total of 1,984 CPV cases in domestic dogs, and 3,593 fox and 3,075 wild dog sightings were reported between 2011 and 2016. Postcodes in which CPV cases were reported were significantly (P = 0.0002) more likely to report wild dogs (odds ratio 2.07, 95% CI 1.41–3.03). Overall, CPV cases were significantly (P < 0.05) correlated with both fox reports (r(SP) 0.225) and wild dog reports (r(SP) 0.247). The strength of association varied by geographical region and year; the strongest correlations were found in the mid-North Coast region (r(SP) 0.607 for wild dogs) and in 2016 (r(SP) 0.481 for foxes). Further serological and virological testing is required to confirm the apparent and plausible association between domestic CPV cases and wild canid distribution found in this study.